Real-time study of on-water chemistry: Surfactant monolayer-assisted growth of a crystalline quasi-2D polymer - Seki, Takakazu; Yu, Xiaoqing; Zhang, Peng; Yu, Chun-Chieh; Liu, Kejun; Gunkel, Lucas; Dong, Renhao; Nagata, Yuki; Feng, Xinliang; Bonn, Mischa (Chem, 2021)
Unlike in the bulk, the hydrogen bond network of water is interrupted at water interfaces, and thus chemical reaction occurs at the water interface in a different manner than in the bulk, owning to, e.g., the possibility of templating molecules. On-water chemistry has generated highly crystalline, functional 2D materials through surfactant-monolayer-assisted interfacial synthesis (SMAIS). Yet, the details of the on-water reaction mechanism have remained unresolved. Here, by tracking the quasi-2D polyaniline film generation process using in situ surface-specific vibrational technique, we clarify how the polymerization reaction occurs at the water surfaces during SMAIS. We identify an aniline derivative with a positively charged terminal =NH2 group as a key reaction intermediate species for highly crystalline film formation. A comparison of differently designed water interfaces reveals that intermediate species can be accumulated and ordered at the interface by the negatively charged surfactant headgroups, prompting highly crystalline, conductive polyaniline film formation. These results demonstrate the importance of interfacial electric fields and electrostatic interactions for controlled on-water chemistry.
CRIS-Team Scopus Importer:2023-03-20
Keywords: 2D polymer; interfacial reaction; on-water chemistry; SDG7: Affordable and clean energy; SDG9: Industry innovation and infrastructure; sum-frequency generation; surface charge; surfactant